ESG disclosure quality and firm valuation under economic policy uncertainty: Evidence from Chinese A-share listed firms - Chia-Hsien Tang; Feifei Luo (PLoS ONE, 2026)
This study examines the extent to which high-quality environmental, social, and governance (ESG) disclosure mitigates the effects of economic policy uncertainty (EPU) on enterprises’ market valuation. The research indicates that utilizing panel data from Chinese A-share listed companies reveals that Economic Policy Uncertainty (EPU) significantly diminishes firm value, whereas robust Environmental, Social, and Governance (ESG) disclosure mitigates this adverse effect. Robustness checks employing alternative variable definitions and subsample analyses based on ownership type, area, and industry corroborate these findings. Mediation analysis indicates that the indirect effects, mediated through a valuation-based channel, reveal that EPU-induced reductions in business value diminish analyst coverage and exacerbate financial distress. These findings offer significant insights for corporate governance, investor decision-making, and regulatory frameworks in emerging nations, as they demonstrate the strategic importance of ESG disclosure in bolstering business resilience against heightened policy risk.